Employment dynamics in Germany: lessons to be learned from the Hartz reforms - Modrack, Simone; Schmid, Günther (Berlin, 2008)
"This paper sets out to explore the black box of recent employment dynamics in Ger-many and thus to identify positive and negative implications that might be of interest for future policymaking. The starting point of our analysis is the question as to whether recent employment growth in Germany is the result of labour market reforms or is instead a mere by-product of the general economic upswing. In order to tackle this ques-tion, we assess German employment performance over the last ten years and also compare the determinants of the latest two economic upturns (1998–2000 and 2005–2007). Guided by an analytical framework that stresses the complementarity of institutions responding to shocks, we examine possible factors behind employment dynamics. The following step is to sum up and discuss the major aspects of the recent German labour market reforms (the so-called Hartz reforms). Taken together, our empirical evi-dence indicates that the recent employment growth might indeed have been facilitated by the labour market reforms. The reforms have led to considerable improvements, but they also demonstrate serious shortcomings."